Microbiological and Rheological Properties of Kefir in Different Combination Medium of Milk and Mung Bean Juice - Setiyawan Ahmad Iskandar; Nurliyani; Widodo; Kurniawan Taufik; Firmansyah Angga Maulana; Pratiwi Diah; Karimy M. Faiz; Febrisiantosa Andi (BIO Web of Conferences, 2025)
Indonesia has quality nut commodities. One of them, mung beans, is known to contain 22.75% protein. Kefir grains include lactic acid bacteria (LAB) in symbiosis with acetic acid bacteria and yeast. Its fermentation produced peptide bioactive, functional properties, probiotics, and inhibitory enzymes. This study evaluated kefir’s microbiological and rheological properties in mixed milk and mung bean juice media. The combination treatment (T) of milk (M) and mung bean juice (MB) as the kefir medium was M 90% + MB 10% (T1), M 80% + 20% MB (T2) and M 70% + 30% MB (T3). The results showed that the LAB and yeast no significantly different in each treatment. Rheological properties of kefir were determined by analyzing sample viscosity at different temperatures (5°C, 20°C, and 30°C). The results showed an increase in the percentage of mung bean juice, and temperature reduced the viscosity value. The highest viscosity value regression was T3 (82.75 mPa·s) at 5°C. The research concluded that combinations of milk and mung bean up to 30% do not affect microbiological properties but affect rheological properties.